2020
DOI: 10.1016/j.eururo.2020.04.068
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Percentage of Prostate-specific Antigen Reduction After Focal Therapy Using High-intensity Focused Ultrasound for Primary Localised Prostate Cancer. Results from a Large Multi-institutional Series

Abstract: Focal therapy (FT) for prostate cancer (PCa) is emerging as a novel therapeutic approach for patients with low to intermediate-risk disease, in order to provide acceptable oncological control, whilst avoiding the side effects of radical treatment. Evidence regarding the ideal follow up strategy, and the significance of PSA kinetics post treatment is needed. In this study we aimed at assessing the value of the percentage of PSA reduction (%PSA reduction) after FT in predicting the likelihood of any additional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 10 publications
2
24
1
Order By: Relevance
“…All patients included in the present study had a reduction of PSA > 75% at three months of follow-up. Even if the percentage of PSA reduction represents only a surrogate of the oncological outcome, Stabile et al recently showed it is inversely associated with disease recurrence and the need for additional treatment, thus potentially useful as a proxy of treatment efficacy [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients included in the present study had a reduction of PSA > 75% at three months of follow-up. Even if the percentage of PSA reduction represents only a surrogate of the oncological outcome, Stabile et al recently showed it is inversely associated with disease recurrence and the need for additional treatment, thus potentially useful as a proxy of treatment efficacy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical and intraoperative biopsy complications were reported using the Clavien-Dindo Classification [15]. Finally, PSA values at three months after therapy were used to compute the percentage of PSA reduction (derived from the ratio between PSA at three months and preoperative PSA) [16].…”
Section: Study Endpoints and Statistical Analysismentioning
confidence: 99%
“…We argue that this might be a better predictor than PSA nadir, given its dependence on pre-salvage PSA. Furthermore, PSA nadir is also influenced by other factors, such as prostate volume [12]. In another study by Peters et al, univariable analysis showed that age was associated with BF in 62 patients treated with whole-gland brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming a 0.05 acceptable difference in apparent and adjusted R-squared, an expected R-squared of 0.15, an overall event rate of 0.2 (200 events per 1000 person-years follow-up), and a shrinkage factor of 0.8, would allow for seven candidate variables with 150 patients and 61 events [25]. For model 1, six candidate variables were selected for multivariable testing based on clinical knowledge and literature [12,17,18]. For model 2, three additional variables were tested, thereby accepting a small increase in chance of overfitting.…”
Section: Candidate Variables For Model Buildingmentioning
confidence: 99%
See 1 more Smart Citation